2023
DOI: 10.3389/fpsyt.2023.1077415
|View full text |Cite
|
Sign up to set email alerts
|

A pilot investigation of differential hydroxymethylation levels in patient-derived neural stem cells implicates altered cortical development in bipolar disorder

Abstract: IntroductionBipolar disorder (BD) is a chronic mental illness characterized by recurrent episodes of mania and depression and associated with social and cognitive disturbances. Environmental factors, such as maternal smoking and childhood trauma, are believed to modulate risk genotypes and contribute to the pathogenesis of BD, suggesting a key role in epigenetic regulation during neurodevelopment. 5-hydroxymethylcytosine (5hmC) is an epigenetic variant of particular interest, as it is highly expressed in the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 99 publications
0
1
0
Order By: Relevance
“…[ 22 ] Several studies demonstrate that hydroxymethylation modification is involved in the migration of placental trophoblast cells and neuronal stem cells. [ 23 , 24 ] Our previous study showed that Nrg1 could be transcriptionally regulated by modification of hydroxymethylation. [ 14 ] Thus, we hypothesized that prenatal 1‐NP exposure restrains interneuron migration through inhibiting hydroxymethylation modification of interneuron migration‐associated genes.…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 ] Several studies demonstrate that hydroxymethylation modification is involved in the migration of placental trophoblast cells and neuronal stem cells. [ 23 , 24 ] Our previous study showed that Nrg1 could be transcriptionally regulated by modification of hydroxymethylation. [ 14 ] Thus, we hypothesized that prenatal 1‐NP exposure restrains interneuron migration through inhibiting hydroxymethylation modification of interneuron migration‐associated genes.…”
Section: Introductionmentioning
confidence: 99%